2016
DOI: 10.1007/s11864-015-0383-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life After Spine Surgery for Primary Bone Tumour

Abstract: Treatment of primary bone tumours (PBT) of the spine is complex, often involving numerous surgical and oncology disciplines. Surgical en bloc resection with oncologically appropriate margins is the modality of choice when treating malignant PBT. En bloc resection with wide or marginal margins appears to offer better local and systemic control of the disease. This type of surgical resection can also be considered when treating benign aggressive tumours such as aneurysmal bone cyst, giant cell tumour and osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
(82 reference statements)
1
14
0
Order By: Relevance
“…Overall, the results of this study describe a trend of better QOL outcomes after PE compared with PES patients, which is supported in the literature . While there was no significant difference between high vs low sacrectomy in sexual function, our results demonstrated that a high level of functional impairment was associated with the procedure independent of the resection level, with only one out of 24 sexual questionnaire responders across both genders having a score indicative of normal function.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, the results of this study describe a trend of better QOL outcomes after PE compared with PES patients, which is supported in the literature . While there was no significant difference between high vs low sacrectomy in sexual function, our results demonstrated that a high level of functional impairment was associated with the procedure independent of the resection level, with only one out of 24 sexual questionnaire responders across both genders having a score indicative of normal function.…”
Section: Discussionsupporting
confidence: 87%
“…En bloc sacrectomy for locally advanced cancer of the pelvis is a complex and morbid procedure. Sacrectomy has evolved to be recognized as the curative treatment of choice for pelvic cancers involving the sacrum but is not offered universally . Sacrectomy is performed as part of a pelvic exenteration involving radical multivisceral resection of locally advanced or recurrent tumours of the pelvis .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the impact of such intralesional strategies on recurrence needs to be studied. 3,5,15,27,28 Treatment of spinal chordoma is clearly evolving. Surgery plays a central role in the management of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…En bloc resection with adequate surgical margins has been shown to decrease rates of recurrence and improve progression-free survival for many primary spinal column tumors and isolated metastatic lesions. 2,3,[6][7][8][11][12][13]16,23 For benign, locally aggressive tumors such as chordomas, 5-year survival rates following piecemeal resection range from 50% to 70% but may be as high as 100% with en bloc removal. 7,8 York et al retrospectively evaluated 27 patients with sacral chordomas and found that patients who underwent en bloc resection with wide margins had an increased disease-free interval compared with patients who underwent intralesional or marginal excision.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although the benefits are well recognized, en bloc resection of spinal tumors is a challenging undertaking due to the difficulty in preserving critical anatomical structures, the requirement for removal of the tumor in one piece, and the need for immediate reconstruction to preserve the mechanical integrity of the spinal column. [6][7][8][9] One systematic review calculated a 36.3% complication rate for en bloc resection of spinal tumors. 8 Another retrospective publication reported that patients undergoing en bloc re-section had longer surgeries, higher rates of both early and late surgical complications, and higher rates of revision when compared with patients who underwent piecemeal resection.…”
Section: Discussionmentioning
confidence: 99%